Measurement Tool for Analyzing the Influence of Brand Ambassador and Social Media Advertising on Brand Loyalty through Brand Trust of Wardah Indonesia - Shafira Dina Kamila; Indrawati, Indrawati (Adpebi Science Series, 2024)
The cosmetics industry is experiencing rapid growth, driven by increasing consumer demand, particularly among women. Companies in personal care and cosmetics industry such as Wardah are actively creating and improving high-quality products to cater to consumer needs and differentiate themselves in the competitive market. The cosmetics market’s tendency shows a relatively low level of brand loyalty in Indonesia. The objective of this research is to develop and validate a measurement tool for assessing how brand ambassadors and social media advertising influence brand loyalty, with brand trust as a mediating factor. The study employed SPSS for data analysis and utilized a purposive sampling approach, focusing on 30 Wardah customers as participants. A preliminary test was conducted to verify the instrument's validity and reliability. The resulting measurement tool consists of 4 variables and 55 items, and it has been deemed appropriate for use in further research.